Simple tools and techniques for enterprise risk management - Chapman, Robert J. (Wiley, 2011)
Your business reputation can take years to build - and mere minutes to destroy. The range of business threats is evolving rapidly but your organization can thrive and gain a competitive advantage with your business vision for enterprise risk management. Trends affecting markets - events in the global financial markets, changing technologies, environmental priorities, dependency on intellectual property - all underline how important it is to keep up to speed on the latest financial risk management practices and procedures. This popular book on enterprise risk management has been expand.- Resumé vydavatel